2020
DOI: 10.1016/j.chemosphere.2020.126345
|View full text |Cite
|
Sign up to set email alerts
|

Multistep partitioning causes significant stable carbon and hydrogen isotope effects during volatilization of toluene and propan-2-ol from unsaturated sandy aquifer sediment

Abstract: Highlights Compound-specific stable isotope analysis is used for monitoring of soil venting Volatilization of toluene and propan-2-ol were studied with C and H isotopes Column experiments with aquifer sediment yielded large isotope effects (IE) A numerical model based on multistep vapor-liquid partitioning reproduces these IE The isotope shifts found here are larger than shifts created by equilibrium processes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The carbon isotope composition of α-HCH was analyzed using a gas chromatograph (Thermo Trace 1310 GC, Thermo Scientific) coupled via a CONFLOW IV (Thermo Scientific, Germany) to a Delta V Advantage mass spectrometer (Thermo Scientific, Germany), as described previously (Zamane et al, 2020). The oxidation furnace of the interface (Thermo Scientific, Germany) containing Pt, Ni, and CuO was set to 1000 C° in order to completely combust α-HCH.…”
Section: Gc-c-irms Analysismentioning
confidence: 99%
“…The carbon isotope composition of α-HCH was analyzed using a gas chromatograph (Thermo Trace 1310 GC, Thermo Scientific) coupled via a CONFLOW IV (Thermo Scientific, Germany) to a Delta V Advantage mass spectrometer (Thermo Scientific, Germany), as described previously (Zamane et al, 2020). The oxidation furnace of the interface (Thermo Scientific, Germany) containing Pt, Ni, and CuO was set to 1000 C° in order to completely combust α-HCH.…”
Section: Gc-c-irms Analysismentioning
confidence: 99%
“…Also, the fundamental understanding of isotope fractionation by sorption/desorption during multi-step partitioning and volatilization should be improved. For instance, a recent study by Zamane et al (2020) showed quite large isotope effects during volatilization of toluene and propan-2-ol from sandy soil. Finally, while stable isotopes are good markers of different sources of pollutants, and markers of sinks, it remains difficult to tease apart both multiple sources and fractionating sinks.…”
Section: Discussionmentioning
confidence: 99%
“…non-equilibrium conditions). During non-equilibrium conditions, not only that the diffusive isotope effect is additive to air-liquid isotope effect, but a number of studies have previously described that the expression of the diffusive isotope effect is impacted by the air volume renewal rate (Bouchard et al, 2008a;Bouchard et al, 2008b;Höhener et al, 2008;Kuder et al, 2009;Julien et al, 2015b;Bouchard et al, 2017a;Zamane et al, 2020). In cases where biodegradation occurs during the VOC transit through the unsaturated soil (as for petroleum hydrocarbons), this third process will also need to be considered to appropriately interpret isotopic trends.…”
Section: Significance For Gas-phase Voc Assessmentsmentioning
confidence: 99%
“…Compound-Specific Isotope Analysis (CSIA) is a process-specific assessment tool increasingly used in gas-phase studies. CSIA was shown to be an appropriate assessment tool to evaluate NSZD in the unsaturated zone (Bouchard et al, 2008b;Höhener et al, 2008;Bouchard et al, 2011), to assess for vapor intrusion (McHugh et al, 2011;Jeannottat and Hunkeler, 2013;Beckley et al, 2016) and to evaluate the performance of remediation systems (Bouchard et al, 2017a;Bouchard et al, 2018b;Zamane et al, 2020). Basically, the CSIA method aims at tracking the isotope ratio evolution of an element ( 13 C/ 12 C, 2 H/ 1 H, 37 Cl/ 35 Cl) for selected VOC with time (and/or distance) to demonstrate VOC biodegradation (Aelion et al, 2010) or to identify the dominant attenuation process (Kuder et al, 2009;Bouchard et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%